A heart of wisdom: Life writing as empathetic inquiry - Watt, Diane (Journal of the Canadian Association for Curriculum Studies, 2013)
This exquisite collection of creative non-‐‑fiction expands possibilities for education through its rich and provocative articulation of life writing as curriculum inquiry. “A Heart of Wisdom: Life Writing as Empathetic Inquiry” (2012) is a companion volume to the editors’ previous work, “Life Writing and Literary Métissage as an Ethos for our Times” (Hasebe-‐‑Ludt, Chambers & Leggo, 2009).